Banks in The Global Integrated Monetary and Fiscal Model - Andrle, Michal (IMF Working Papers; Working Paper ;, 2015)
The Global Integrated Monetary and Fiscal model (GIMF) is a multi-region DSGE model developed by the Economic Modeling Division of the IMF for policy and scenario analysis. This paper compares two versions of GIMF, GIMF with a conventional financial accelerator, where bank balance sheets do not play a prominent role, and GIMF with both a financial accelerator and a fully specified banking sector that can make lending losses, and that is regulated according to Basel-III. We illustrate the comparative macroeconomic properties of both models by presenting their responses to a wide range of fiscal, demand, supply and financial shocks.